PENGEMBANGAN LITERASI DASAR UNTUK MENUMBUHKAN MINAT BACA ANAK - ANAK DESA KUMBANG MELALUI PROGRAM PERPUSTAKAAN NASIONAL - Maulana, Daffa; Syahbudin, Meuthia Nandika; Utami, Davina Putri; Hidayati, Wahyu Siti; Handayani, Erna; Anugrah, Muhammad Naufal; Rahman, Abianda Aimar; Febriani, Laura; Pratiwi, Sriana; Cayaano, Arsy Masqaidah (Universitas Mataram, 2025)
The Community Service Program (Kuliah Kerja Nyata-KKN) is a mandatory program for Mataram University students to implement the Tri Dharma of Higher Education, which aims to make a real contribution to society through community service. The 2025 National Library Literacy KKN PMD activity was held in Kumbang Village with a focus on improving children's and community literacy culture. The background to this activity stems from the low interest in reading and literacy skills among village children. The goal of the activity is to improve children's basic literacy skills through a creative and interactive approach based on reading books. The activity method used is an interactive approach based on the National Library's literacy program, including reading aloud, creative projects, book reviews, and story writing. The target of this activity is the children of Kumbang Village. This approach aims to ensure that children are not only able to read, but also encouraged to think critically, imagine and express themselves. The results of the activity show an increase in children's active participation in reading, an increase in understanding of the reading content, and the ability to express ideas in the form of creative works. This activity strengthens social interactions between children and fosters community enthusiasm for the village literacy program. In addition, the KKN Group is also involved in other activities as a form of developing children's basic literacy, namely Literacy Appreciation, Literacy Competitions, Literacy Visits to Schools and Literacy Posyandu. The results of the above activities show that the synergy between students, the community and national institutions such as the National Library can make a real contribution to the development of basic literacy. In conclusion, the KKN Literacy activity has proven effective in increasing children's interest in reading, reading comprehension, and creative literacy skills.